2023
DOI: 10.3390/pathogens12070874
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Postbiotics as an Alternative to Antibiotics: An Emphasis on Pigs

Abstract: Probiotics are being used as feed/food supplements as an alternative to antibiotics. It has been demonstrated that probiotics provide several health benefits, including preventing diarrhea, irritable bowel syndrome, and immunomodulation. Alongside probiotic bacteria-fermented foods, the different structural components, such as lipoteichoic acids, teichoic acids, peptidoglycans, and surface-layer proteins, offer several advantages. Probiotics can produce different antimicrobial components, enzymes, peptides, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 178 publications
0
11
0
Order By: Relevance
“…Numerous studies have shown that plant proteins have a regulatory effect on intestinal flora. 42 Beneficial bacteria promote good health by strengthening the immune system, 43 improving digestion and absorption, 44 producing vitamins, inhibiting the growth of potential pathogens 45 and preventing the feeling of gas and bloating. 46 However, harmful bacteria make carcinogens, decay proteins in the gut, produce toxins, and disrupt our intestinal functioning, leading to bacterial infections and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that plant proteins have a regulatory effect on intestinal flora. 42 Beneficial bacteria promote good health by strengthening the immune system, 43 improving digestion and absorption, 44 producing vitamins, inhibiting the growth of potential pathogens 45 and preventing the feeling of gas and bloating. 46 However, harmful bacteria make carcinogens, decay proteins in the gut, produce toxins, and disrupt our intestinal functioning, leading to bacterial infections and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since platinum nanoparticles are widely utilized in medical applications (Mikhailova, 2022 ), the combination of platinum nanoparticles and traditional antibiotics provides a promising approach to combat antibiotic‐resistant P. aeruginosa . Probiotics are used as dietary supplements which provide multiple health benefits (Ali et al., 2023 ). It was recently shown that probiotic cell‐free supernatants significantly increase the expression of oprD and decrease the expression of several efflux operons such as mexAB‐oprM , mexCD‐oprJ , and mexEF‐oprN (Mehboudi et al., 2023 ), highlighting a therapeutical potential with the combination of probiotics and antibiotics.…”
Section: Anti‐resistance By Modulating Antibiotic Influx and Efflux M...mentioning
confidence: 99%
“…Postbiotics have been explored for their roles in immune modulation, as antioxidants, chemopreventive agents, and antimicrobial adjuncts and alternatives ( Kumbhare et al, 2023 ). Specifically, postbiotics, prepared with lactic acid bacteria, a diverse group of probiotic strains native to human and animal microbiotas, have been increasingly explored for their roles in antimicrobial activity, including as anti-biofilm agents for interference with quorum sensing, for enhancing the growth of other beneficial microbial symbionts, as applications to food products or used, and in animal production systems to attenuate antimicrobial use ( Ali et al, 2023 ; Chuah et al, 2023 ; Kudra et al, 2023 ; Kumbhare et al, 2023 ; Penchuk et al, 2023 ; Sepordeh et al, 2023 ; Sharafi et al, 2023 ; Tong et al, 2023 ). Across postbiotic studies, there remains a knowledge gap in understanding postbiotic mechanisms of action, including incomplete characterization of the bioactive small molecules driving these diverse functions ( Kumbhare et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Across postbiotic studies, there remains a knowledge gap in understanding postbiotic mechanisms of action, including incomplete characterization of the bioactive small molecules driving these diverse functions ( Kumbhare et al, 2023 ). This includes how both probiotic strain and prebiotic selection impact the function of postbiotics ( Ali et al, 2023 ; Kumbhare et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%